2022
DOI: 10.3390/su14138165
|View full text |Cite
|
Sign up to set email alerts
|

Urban Air Quality Monitoring in Decarbonization Context; Case Study—Traditional Coal Mining Area, Petroșani, Romania

Abstract: Humanity is a fossil-fueled civilization with a large influence on the environment. The World Health Organization (WHO) has pointed out that air pollution is now the single biggest environmental threat to human health. The air quality in Petroșani, a traditional mining region from the Jiu Valley bituminous coal basin, Romania, is rarely debated; however, it is not often investigated. In this paper, the main air pollution sources of Petroșani are identified and the performed measurements emphasize the air quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The mining waste facilities in Romania are designed, built and checked according to technical prescription PT-C 39 [1]. This technical prescription contains several criteria for mining waste facilities classification [2,3].…”
Section: Characteristics Of Livezeni Tailings Dumpmentioning
confidence: 99%
“…The mining waste facilities in Romania are designed, built and checked according to technical prescription PT-C 39 [1]. This technical prescription contains several criteria for mining waste facilities classification [2,3].…”
Section: Characteristics Of Livezeni Tailings Dumpmentioning
confidence: 99%
“…Several case studies [2,3,7] analysed the air quality in Petrosani, each one analysing in particular the impact generated by road traffic on air quality and implicitly on the health of population. The new environmental objectives included in the Economic, Social and Environmental Development Strategy of the Jiu Valley (2022-2030) refer to environmental monitoring in all 6 jurisdictions, which will contribute to a much broader analysis of air quality and population health.…”
Section: Fig2 Measurement Locations (Measurement Points)mentioning
confidence: 99%
“…These houses were designed in a specific architectural style, with a single level and adjacent garden plots. It is a neighborhood where many families with modest material possibilities currently live [3,13]. Unfortunately, despite the beauty and cultural value of the Historical Center of Petroșani, this area has become one of the most polluted in the city due to the low standard of living and the lack of alternative heating sources.…”
Section: Description Of the Studied Areamentioning
confidence: 99%
“…All this, combined with an alarming increase in the number of oncological patients in the area, forces a different approach to highlight through comparative studies the influence of different sources of air pollution and, as far as possible, their quantification. At different levels of depth, the documentation of the subject was started about four years ago by collectives that did not lack students, masters or doctoral students and the collective of authors, with different responsibilities and contributions [2, 3,4,5]. Thus, two important sources were identified that negatively influence the air quality in the analyzed area, namely the noxious gases and Particulate Matters resulting from the increase of the number of vehicles and implicitly the values of road traffic [6], but also as a result of the systematic burning of some fuels and/or/especially cloth and footwear waste in the historic districts of the cities.…”
Section: Introductionmentioning
confidence: 99%